2022
DOI: 10.1136/bmjopen-2022-063870
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce stigma related to contraception and abortion: a scoping review

Abstract: ObjectivesWe conducted a scoping review to identify the types, volume and characteristics of available evidence and analyse the gaps in the knowledge base for evaluated interventions to reduce contraception and abortion stigma.DesignWe conducted a search of five electronic databases to identify articles published between January 2000 and January 2022, and explored the websites of relevant organisations and grey literature databases for unpublished and non-commercial reports. Articles were assessed for eligibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Training can help providers develop proactive strategies to overcome the common stigma-related barriers that abortion seekers may encounter, including conscientious objection and gatekeeping. Stigma-reduction strategies are also of relevance to other maternal and reproductive health services, where clients may be disrespected, stigmatized, mistreated, and their preferences not considered (55,60).…”
Section: Improving Quality Of Care By Addressing Abortion Stigmamentioning
confidence: 99%
See 3 more Smart Citations
“…Training can help providers develop proactive strategies to overcome the common stigma-related barriers that abortion seekers may encounter, including conscientious objection and gatekeeping. Stigma-reduction strategies are also of relevance to other maternal and reproductive health services, where clients may be disrespected, stigmatized, mistreated, and their preferences not considered (55,60).…”
Section: Improving Quality Of Care By Addressing Abortion Stigmamentioning
confidence: 99%
“…Recent systematic and scoping reviews have identi ed a need for theory-based and tested stigma reduction interventions (2,55,56). This study contributes by identifying speci c behaviors -both positive and negative -on which stigma reduction strategies could focus.…”
Section: Improving Quality Of Care By Addressing Abortion Stigmamentioning
confidence: 99%
See 2 more Smart Citations
“…Little research has investigated the association between exposure to television abortion plotlines and viewer abortion knowledge, attitudes, and behaviors. Indeed, a recent scoping review found only two studies analyzing the relationship between abortion portrayals and viewer attitudes over a ten-year period (Sorhaindo & Loi, 2022). The present study uses a quasi-experimental ex post facto design with an online sample of natural viewers of three television shows with abortion plotlines to examine if viewers exposed to any of the three abortion plotlines (and to each of the three individual plot lines) were more likely to have greater knowledge about abortion compared to unexposed audiences (Hypothesis 1), lower stigmatizing attitudes towards abortion compared to unexposed audiences (Hypothesis 2), and higher willingness to support a family member or friend seeking an abortion compared to unexposed audiences (Hypothesis 3).…”
mentioning
confidence: 99%